2018
DOI: 10.1037/cap0000146
|View full text |Cite
|
Sign up to set email alerts
|

Psychological aspects of medical assistance in dying: A personal reflection.

Abstract: Bill C-14 introduces a new era in end-of-life care by permitting death to be hastened through medical assistance in dying (MAiD). This article reviews those aspects of MAiD that are of particular relevance to psychologists, as seen through the perspective of the author's research. It includes a brief overview of the major legal cases that led the Supreme Court of Canada to overturn the laws against assisted suicide. It addresses such issues as the prevalence of the desire for death in the terminally ill, reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Psychologists working with terminally-ill people should anticipate that their clients might want to talk to them about hastening their deaths. Qualitative researchers found that terminally-ill people frequently think about death, dying and suicide (Courage et al, 1993) and quantitative researchers found that 25% of terminally-ill people desire to hasten their deaths (see Brown, Henteleff, Barakat, & Rowe, 1986;Wilson, 2018). Courage et al (1993) found that they rarely mention their thoughts about hastening deaths to their supporters (also see Pallative Care Australia, 2018).…”
Section: Ends Of Their Lives: a Western Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Psychologists working with terminally-ill people should anticipate that their clients might want to talk to them about hastening their deaths. Qualitative researchers found that terminally-ill people frequently think about death, dying and suicide (Courage et al, 1993) and quantitative researchers found that 25% of terminally-ill people desire to hasten their deaths (see Brown, Henteleff, Barakat, & Rowe, 1986;Wilson, 2018). Courage et al (1993) found that they rarely mention their thoughts about hastening deaths to their supporters (also see Pallative Care Australia, 2018).…”
Section: Ends Of Their Lives: a Western Perspectivementioning
confidence: 99%
“…Psychologists should therefore cautiously explore their terminally-ill clients' desire to die (Gupta et al, 2005) taking into account the theories of suicide and how to interpret such ideation (see Wilson, 2018). Most terminally-ill people do not desire to die (Wilson, 2018), but some without mental health diagnoses have genuine and consistent desires to die because they are ready to die (Nissim et al, 2009) or for a variety of other reasons (Muskin, 1998).…”
Section: Clients Who Desire To Diementioning
confidence: 99%